H-point Standard Addition Method (HPSAM) for Simultaneous Spectrophotometric Determination of Cu(II) and Pd(II) by 1-(2-thiazolylazo)-2-naphthol (TAN) in Micellar Media. Issue 2 (3rd March 2016) - Bagherian, Ghadamali; Arab Chamjangali, Mansour; Mohammadian, Hamideh
Abstract: The H-point standard addition method (HPSAM) is proposed for the simultaneous determination of Cu(II) and Pd(II). It is a simple, selective, and sensitive, spectrophotometric method. The basis of this technique is the complex formation of Cu(II) and Pd(II) with 1-(2-thiazolylazo)-2-naphthol (TAN) at pH 2.2, and in the presence of sodium dodecyl sulfate (SDS) as a micellizing agent. The sensitivity and selectivity of the method improve in the presence of a micellar system and an acidic medium, respectively. Cu(II) and Pd(II) can be determined in the concentration ranges of 0.04-3.40 and 0.12-6.0 μg mL -1 with satisfactory accuracy and precision. The proposed method was used for the simultaneous determination of Cu(II) and Pd(II) in water and various synthetic alloy samples with different concentration ratios of Cu(II) and Pd(II) with good accuracy and precision.